Post-Treatment Neurocognitive Disorders in Adults with Frontal or Parietal Astrocytomas - Salek, Roham; Anvari, Kazem; Fanipakdel, Azar; Parsamanesh, Roya; Mojtaba Ejlalzadeh, Seyyed; Rahimy, Nafise; Javadinia, Seyed Alireza (Reports of Radiotherapy and Oncology, 2016)
Background: High-grade astrocytomas are among the most common neuroepithelial brain tumors. Because of their highly malignant nature, in most cases, in addition to maximal resection, they also require adjuvant treatments, such as chemotherapy and radiotherapy. A common accompanying condition, which may occur with this type of clinical presentation, is cognitive disorders. These can be caused by the tumor itself, the treatment used or may be patient related. The aim of this study was to evaluate the level of cognitive ability in patients with astrocytoma compared to the normal population and evaluating the factors possibly affecting them. Methods: A case-control study was performed on 30 adults referred to Imam Reza and Omid hospitals, Mashhad, Iran, during year 2014. The studied patients had astrocytomas, for which they had performed surgery. All patients had also received radiotherapy. The control group consisted of 30 healthy individuals, among the patients’ family members, who were matched for age and gender with the patients. The tools used in this study were a checklist for demographic data, and the Farsi version of Addenbrook’s cognitive questionnaire. Data were entered in the SPSS 22 software and analyzed using the Student’s t test and Mann-Whitney test. P values of ≤ 0.05 were considered significant. Results: Normal cognitive disorders were seen in 33.3% and 80% of the patient and control groups, respectively. Mild cognitive disability was observed in 10% of both groups; and Alzheimer’s was observed in 56.7% and 10% of the patient and control groups, respectively. A statistically significant difference was found between cognitive function, age, and gender (P = 0.0001 in both). No meaningful difference, however, was observed between cognitive score and tumor location, chemotherapy, and the time, from which treatment had ended. Conclusion: With the high prevalence of cognitive disorders among patients with astrocytoma, one can conclude that the tumor itself and the surrounding factors affect the cognitive function of the patient. Results of this study showed that the type of treatment and some properties of the tumor, such as the tumor’s location, do not affect the patient’s cognitive capacity.